TUNJUK AJAR MELAYU RIAU - Hj. Efni Ramli (AL-ISHLAH: Jurnal Pendidikan, 2016)
Malay culture is one of the supporting pillars of the national culture in Indonesia. Malay culture influences from the outside, but it does not change the basic structure of the Malay culture. Malay culture has proven its ability in accordance with Malay motto “tak lekang karena panas tak lapuk karena hujan“. So, it needs to be continued and preserved. Form of Malay culture is very diverse. This can be oral and written. This is also in the form of poems and rhymes. Malay teachings have many messages in accordance with the teachings of Islam. The Malay culture is identical to Islam.